Parenting Autism: Exploring Social Support and Religiosity - Restu Utami; Diah Krisnatuti; Irni Rahmayani Johan (Indigenous: Jurnal Ilmiah Psikologi, 2025)
Abstract. Raising children with autism presents ongoing emotional and psychological challenges. The aim of this research is to explore how social support and religiosity influence the well-being of parents raising children with autism. Following the PRISMA framework, this review analyzed 45 studies through a systematic literature review approach. The studies were selected using the PECO framework and assessed for quality with the Q-SSP and ROBINS-E tools. The participants in the reviewed studies consisted of parents or caregivers, with varying demographics, including age, gender, cultural background, and levels of religiosity. Various data collection techniques were employed, including qualitative interviews, quantitative surveys, and mixed-method approaches; analysis methods included thematic interpretation and statistical modeling. Findings show that social support reduces stress and improves coping abilities, particularly when parents receive consistent support from partners and communities. Religiosity contributes as a psychological and emotional coping resource by offering meaning, comfort, and resilience, though in certain contexts it may also lead to feelings of guilt or stigma. The influence of both factors varies across cultural and social settings. The results highlight the distinct but complementary roles of social support and religiosity in strengthening parental well-being. Integrating these elements into culturally sensitive intervention models may enhance support systems for parents. Future research should aim to examine integrative approaches that connect social and spiritual support strategies. Keywords: autism spectrum disorder; parental well-being; religiosity; social support; systematic review.